A Educação Especial no estado de São Paulo no contexto da primeira república: uma análise da construção histórica dos alunos anormais e das propostas pedagógicas - Oliveira, Isabelle Karolline Chaves de (Universidade Federal de São Carlos, 2021)
In this work, we set out to investigate how, the historical construction of the “abnormal” student and the pedagogical proposals aimed at this student profile in the context of the First Republic, having a central role in this process, the republican education project, expressed in the model of School Groups, as a civilizing landmark for a modern society. This research is structured and develops from three chapters. In the first chapter, we bring the reader an initial overview, contextualizing about the modernization of Brazilian society, which unfolded during the First Republic, about its political, cultural, economic aspect and the issue of education, highlighting the civilizing project of school groups, since the republican ideal, which places education as a redemptor of social problems, the school model and its representation as the motto of the republic. The second chapter discusses the historical production of the “abnormal” student, from the historical understanding with the advent of modernity and capitalist society, as well as that same issue in the Brazilian reality, the theories and proposals formulated by some important intellectuals used as a reference by the Instruction Pública Paulista in the first Republic linked to inequality and what education was thought for this project in the new modern society, bringing up the issue of the poor student and the handicapped. In this sense, the last chapter brings the documentary analysis of the yearbooks of public education in São Paulo between 1907-1926 and the document of the medical inspection of 1917, in order to analyze the pedagogical proposals thought by the directors and inspectors of public education, for those who did not attend to the expectations created for modern education, since the creation of school groups, the concept of school and education and those that should be considered unfit for the new society and, therefore, should be adjusted to the needs of the market.
Special Education in the state of São Paulo in the context of the first republic: an analysis of the historical construction of abnormal students and pedagogical proposals
Keywords: História da Educação; Educação Especial; Primeira República; Instrução Pública Paulista; History of Education; Special education; First Republic; Paulista Public Instruction; CIENCIAS HUMANAS::EDUCACAO